Desenvolvimento de novos complexos fosfínicos de rutênio com potencial anticâncer e bactericida - Carvalho, José Marcos da Silveira (2018)
In this work, it were synthetized phosphinic ruthenium II complexes containing the biological interesting ligands quinone derivatives and dppz (dipyrido[3,2-a:2',3'-c]phenazine). After that, carbon monoxide ligand (CO) was added to the complexes in order to combine the pharmacological properties described to the CO in the CORM (carbon monoxide release molecule) complexes with the anticancer activity of those ligands, boosting the antitumor action of this new series of complexes and minimizing the side effects to the organism. The synthetized complexes were characterized through electrochemical and spectroscopic techniques, and the experimental results were compared to the ones obtained from DFT (Density Functional Theory) studies. Electrochemical measures showed coherence with the spectroscopic assays, which ones agreed with the theoretical studies, suggesting the selected basis for the DFT calculations are able to describe both electronic and vibrational profiles of the complexes. A correlation was observed among the ring substituents in the quinone ligands, in which electronic density acceptor ligands stabilizes the complexes orbitals and electronic density donors substituents enhance the energy of those orbitals. That observation can be useful to the planning of new optimized compounds that intends to reduce the energy necessary to the occurrence of photochemical reactions, facilitating their use in photodynamic therapy. In vitro cytotoxic assays demonstrated the synthetized complexes presented antineoplastic potential against the tumor cell lines HCT-116 (colon) and PC-3 (prostate). Bactericide effect was also observed against gram-positive cultures.